Designing an Investment Policy Analysis Model for Oil Production Using System Dynamics Method - Heydarinia, Manochehr; Makvandi, Foad; Ghasemiyeh, Rahim; Chenari, Vahid; Amirnejad, Ghanbar (International Journal of Innovation Management and Organizational Behavior (IJIMOB), 2023)
Objective: The objective of this research was to design a model for analyzing investment policies in oil production using content analysis and the Delphi method and the system dynamics method.Methodology: The statistical population for content analysis included upstream documents of the oil industry and articles related to investment in oil production available on the Ministry of Oil's website and a comprehensive article database, amounting to 29 articles related to investment in the oil industry. Based on the acquisition method, 9 articles were selected for content analysis. In the Delphi section, officials, managers, and deputies of this company, along with university professors in public administration in Khuzestan province, totaling 32 individuals, were included in the statistical population, and 15 individuals were selected as the statistical sample using a purposive stratified method. In the quantitative section, the statistical population included all employees, managers, official experts, and employed personnel of the National Iranian South Oil Company in Ahvaz, totaling 570 individuals. Using the simple sampling method and based on Cochran's formula and random method, 291 individuals were calculated as the statistical sample.Findings: After confirming the dimensions and components in the Delphi system dynamics section using Vensim software, 9 scenarios were considered: 1- Reduction of unfavorable monetary policies, 2- Improvement of financial assessments, 3- Improvement of investment source diversity, 4- Structural development of oil extraction and production, 5- Improvement of research and development policies in the oil industry, 6- Improvement of financing based on underground reserves, 7- Improvement of debt-based financing, 8- Improvement of intermediary financing, 9- Improvement of policies for the introduction of oil technologies.Conclusion: Therefore, in this loop, the assumption is that potential risks affect monetary policies, financial assessment, and investment management. Investment management reduces socio-cultural factors, and when socio-cultural factors decrease, it increases environmental neglect. The more environmental neglect increases, the production ceiling in the oil industry is likely to decrease. These factors ultimately cause the tendency to weaken investment policies in oil production.